STEAM-Based Authentic Assessment in Improving Physics Students’ Critical Thinking Skills: A Systematic Literature Review - Fiskawarni, Tri Hastiti; Bancong, Hartono; Sukmawati, Sukmawati (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study examines the effectiveness of authentic assessment based on STEAM (Science, Technology, Engineering, Arts, and Mathematics) in improving physics students’ critical thinking skills through a PRISMA-based systematic literature review (SLR) of publications from 2020–2025. The search was conducted in Scopus, Web of Science, DOAJ, and Google Scholar using the keywords: (“STEAM” OR “STEM+Arts”) AND (“authentic assessment” OR “performance assessment” OR “project-based assessment” OR “rubric”) AND (“critical thinking”) AND (“physics education” OR “physics students”). After removing duplicates and screening titles/abstracts according to inclusion criteria (peer-reviewed empirical studies, STEAM-based assessment in physics or closely related science-physics contexts, reporting critical thinking outcomes), 58 eligible articles were retained for full analysis. The final corpus consisted of quasi-experimental/intervention studies, classroom action research, and mixed-methods designs, predominantly at undergraduate and upper-secondary levels, with most studies conducted in Asia (especially Indonesia) and Europe. The synthesis shows that authentic STEAM-based assessments significantly improve critical thinking skills, especially in analysis (28%), evaluation (32%), and creation (35%), with effective strategies including interdisciplinary projects, technology-supported simulations, and collaborative teamwork. Across studies reporting effect sizes, the mean effect was in the moderate-to-large range (Cohen’s d = 0.72). This approach aligns with Vygotsky’s constructivism and Bloom’s taxonomy by promoting contextual learning and active student engagement. Nevertheless, implementation faces challenges such as limited resources, uneven student readiness, and potential subjectivity in scoring. The study recommends lecturer training, rubric development, and the use of accessible technologies to strengthen STEAM assessment practices in Indonesia and comparable contexts. Further experimental validation and local adaptation are recommended.